The Javanese kris - Groneman, I. (Isaac) (Zwartenkot Art Books KITLV Press, 2009)
The kris is both a weapon and spirital object. This book is the first English translation of a definitive four-part article originally published between 1910 and 1913, describing the forging of a number of blades and the manufacture of the other parts of the kris, placed in a broad historical and cultural framework